Manuscripts of Qādir ʿAli beg’s historical work Jāmiʿ at-Tawārīkh ‘Compendium of Chronicles - Тогабаева, Гүлдана (Turkic Studies Journal, 2022)
Jāmiʿ at-Tawārīkh ‘Compendium of Chronicles’ is the Qādir ʿAli beg’s historical work written in 1602. The primary source of this work more likely did not reach our days. However, today two lists (St. Petersburg manuscript and Kazan manuscript), three fragments (a fragment from Kyshgary, a fragment from the first London manuscript, and a fragment from the second London manuscript), and two more manuscripts (Paris manuscript and Berlin manuscript) are known as related to the Qādir ʿAli beg’s ‘Compendium of Chronicles’, although the authorship of the last two manuscripts is questionable. The article analyses all currently known lists and fragments of Qādir ʿAli beg’s work. The study did not identify major textological discrepancies among the two lists and three fragments except for some minor differences in spelling. The two lists complement each other and most probably were copied from the same source. The fragments of the work do not carry any additional information from the one present in the lists; hence, they do not carry any textological value. However, the fragments are important evidence of the significance of Qādir ʿAli beg’s work. The location of London manuscripts is of particular interest, raising the question of the appearance of two fragments that are found in the ‘Compendium of Chronicles’ in Britain. A feature of the London manuscripts is the presence in the text of postscripts from the margins of the St. Petersburg manuscript, presented as a concordance of words.